Author Correction: A mixed antagonistic/synergistic miRNA repression model enables accurate predictions of multi-input miRNA sensor activity. Issue 1 (December 2018) - Gam, Jeremy; Babb, Jonathan; Weiss, Ron
In the originally published version of this Article, financial support was not fully acknowledged. The PDF and HTML versions of the Article have now been corrected to include support from the National Science Foundation (NSF), award number 1745645.